Pengaruh Pembiayaan Modal Usaha Dan Inovasi Produk Terhadap Perkembangan Usaha Masyarakat Kecamatan Lubuk Besar: (Studi Pada Permodalan Nasional Madani Mekar Syariah) - Hidayah, Imroatul; Purwanto, Tinggal; Fahlevi, Mahfudz Reza (PROGRAM STUDI AKUNTANSI SYARIAH FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are one of the main drivers of national economic growth, playing a crucial role in establishing a healthy economic structure and performance. The government demonstrates its support for MSME actors through financing initiatives, one of which is provided by Permodalan Nasional Madani (PNM), which since 2015 has offered capital loans to underprivileged women entrepreneurs. This study aims to determine the influence of business capital financing and product innovation on the business development of communities in Lubuk Besar District, particularly the clients of PNM Mekar Syariah. This research uses a quantitative approach with primary data. The population consists of 2,903 individuals, with 97 respondents selected using a random sampling technique. Data analysis was conducted through validity and reliability tests, classical assumption testing, multiple regression analysis, and hypothesis testing with the assistance of SPSS version 30.0. The results of the study show that partially, business capital financing has a significant effect on business development (significance < 0.001; t-count = 3.488 > t-table = 1.985). Product innovation also shows a significant influence (significance = 0.009; t-count = 2.672 > t-table). Simultaneously, both variables significantly affect business development (F-count = 25.317 > F-table = 3.09). The contribution of these two variables to business development is 35%, while the remaining 65% is influenced by other factors not examined in this study.